Teaching Ad Tech: Assessing Collaborative Teaching in an Advertising, Computer Science and Design Course. (November 2017) - Newell, Jay; Tavanapong, Wallapak; Berghefer, Sherry
Advertising technology is advancing quickly incorporating digital techniques that may be beyond the experience of the individual faculty member. Collaborative teaching, where faculty members from different disciplines co-teach a course, may be a solution. This report assesses the learning outcomes of an advertising technology course taught by faculty from one university's advertising, computer science and human-computer interaction programs. The course was run twice, with a third one in progress. Students were predominantly advertising majors, with a minority of computer science and design majors. Two semesters of pre- and post-tests were analyzed, finding increases in student comfort with preparing and presenting technologically advanced solutions to advertising challenges.